2016
DOI: 10.1016/j.knee.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to “The course and distribution of the infra patellar nerve in relation to ACL reconstruction” [Knee 22 (2015) 384–388]

Abstract: ErratumErratum to "The course and distribution of the infra patellar nerve in relation to ACL reconstruction" [Knee 22 (2015) 384-388] The publisher regrets that in the above article, references 6 and 22 are the same. The publisher would like to apologise for any inconvenience caused.The Knee 23 (2016) 1174 DOI of original article: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The IPBSN was found to have a highly variable coarse, the most common variant being the posterior pathway in 56% of the knees (arising along the inferior posterior border of the sartorius muscle), found alone in 28%, and in association with the intramuscular (piercing through the sartorius muscle) and/or the anterior pathway (anterior border of the sartorius muscle) in 28%. Walshaw et al [ 31 ] also concluded that the IPBSN is mostly damaged during tendon harvesting with the stripper owing to its close proximity to the ST and GT.…”
Section: Graft Harvestingmentioning
confidence: 99%
“…The IPBSN was found to have a highly variable coarse, the most common variant being the posterior pathway in 56% of the knees (arising along the inferior posterior border of the sartorius muscle), found alone in 28%, and in association with the intramuscular (piercing through the sartorius muscle) and/or the anterior pathway (anterior border of the sartorius muscle) in 28%. Walshaw et al [ 31 ] also concluded that the IPBSN is mostly damaged during tendon harvesting with the stripper owing to its close proximity to the ST and GT.…”
Section: Graft Harvestingmentioning
confidence: 99%